2008
DOI: 10.1534/genetics.108.092577
|View full text |Cite
|
Sign up to set email alerts
|

A Genomewide Suppressor and Enhancer Analysis of cdc13-1 Reveals Varied Cellular Processes Influencing Telomere Capping in Saccharomyces cerevisiae

Abstract: In Saccharomyces cerevisiae, Cdc13 binds telomeric DNA to recruit telomerase and to ''cap'' chromosome ends. In temperature-sensitive cdc13-1 mutants telomeric DNA is degraded and cell-cycle progression is inhibited. To identify novel proteins and pathways that cap telomeres, or that respond to uncapped telomeres, we combined cdc13-1 with the yeast gene deletion collection and used high-throughput spot-test assays to measure growth. We identified 369 gene deletions, in eight different phenotypic classes, that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
92
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(100 citation statements)
references
References 71 publications
8
92
0
Order By: Relevance
“…5A). Previously, it was found that Rif2 and Rif1 have synergistic effects in inhibiting telomerase (Wotton & Shore, 1997; Levy & Blackburn, 2004) and yet opposing effects in regulating the proliferation of telomere‐dysfunctional cdc13‐1 cells (Addinall et al ., 2008; Xue et al ., 2011). In conclusion, Rif1 is unique among many telomere‐associated proteins in facilitating proliferation of cells lacking telomeres, whereas Rif2 and Mre11 have the opposite effect to Rif1.…”
Section: Resultsmentioning
confidence: 99%
“…5A). Previously, it was found that Rif2 and Rif1 have synergistic effects in inhibiting telomerase (Wotton & Shore, 1997; Levy & Blackburn, 2004) and yet opposing effects in regulating the proliferation of telomere‐dysfunctional cdc13‐1 cells (Addinall et al ., 2008; Xue et al ., 2011). In conclusion, Rif1 is unique among many telomere‐associated proteins in facilitating proliferation of cells lacking telomeres, whereas Rif2 and Mre11 have the opposite effect to Rif1.…”
Section: Resultsmentioning
confidence: 99%
“…Many of the genes hit were involved in genetic processes such as DNA metabolism, chromatin remodeling, transcription, and replication; others were involved in additional cellular processes, such as cell membrane integrity, vesicle transport (particularly to the vacuole), mitochondrial proteins, and scaffold proteins or had unidentified functions. We investigated whether or not the genes isolated from our screen had previously been isolated in screens for genes that disrupt telomeric-related functions (Singer et al 1998;Smith et al 1999Smith et al , 2004Andrulis et al 2002;Teixeira et al 2002;Askree et al 2004;Gatbonton et al 2006;Addinall et al 2008;Shachar et al 2008). We found 13 genes: YKU80, STO1, HPR5, SGS1, RAD17, RAD24, HFI1, PHB2, APN1, IRC7, PCK6, RNR3, and UFD2 ( Figure S1) that had previously been isolated in screens for genes that affect telomere length and capping mechanisms (Askree et al 2004;Gatbonton et al 2006;Addinall et al 2008;Shachar et al 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Using data from the SGD, we found that 23 of the genes hit in our screen had some kind of interaction with another gene from our screen. Furthermore, 38 genes from our screen had physical or genetic interactions with the genes identified in previous screens (Askree et al 2004;Gatbonton et al 2006;Addinall et al 2008;Shachar et al 2008). We compiled a list using data from the SGD that contained all GO annotations, protein interactions, and genetic interactions for each of the genes hit in our screen (Table S3).…”
Section: Resultsmentioning
confidence: 99%
“…Deletion of the gene encoding maintenance of telomere capping protein 2 in Z. rouxii results in a phenotype more susceptible to telomere-shortening related cell-cycle arrests when exposed to heat stress (Addinall et al 2008). The mechanism by which this protein protects the telomere cap is not known, but if it serves the same function in T. aggressivum then a decrease in the amount of this protein may lead to reduced cell longevity.…”
Section: Discussionmentioning
confidence: 99%